Diversity in genome size and GC content shows adaptive potential in orchids and is closely linked to partial endoreplication, plant life‐history traits and climatic conditions. Issue 4 (9th October 2019) - Trávníček, Pavel; Čertner, Martin; Ponert, Jan; Chumová, Zuzana; Jersáková, Jana; Suda, Jan
Summary: In angiosperms, genome size and nucleobase composition (GC content) exhibit pronounced variation with possible adaptive consequences. The hyperdiverse orchid family possessing the unique phenomenon of partial endoreplication (PE) provides a great opportunity to search for interactions of both genomic traits with the evolutionary history of the family. Using flow cytometry, we report values of both genomic traits and the type of endoreplication for 149 orchid species and compare these with a suite of life‐history traits and climatic niche data using phylogeny‐based statistics. The evolution of genomic traits was further studied using the Brownian motion (BM) and Ornstein–Uhlenbeck (OU) models to access their adaptive potential. Pronounced variation in genome size (341–54 878 Mb), and especially in GC content (23.9–50.5%), was detected among orchids. Diversity in both genomic traits was closely related to the type of endoreplication, plant growth form and climatic conditions. GC content was also associated with the type of dormancy. In all tested scenarios, OU models always outperformed BM models. Unparalleled GC content variation was discovered in orchids, setting new limits for plants. Our study indicates that diversity in both genome size and GC content has adaptive consequences and is tightly linked with evolutionary transitions to PE.